Design of Assessment System of AI Educational Model for Elementary Student - Seok-Jae Moon; Kibbm Lee; Jong-Yong Lee (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the AI education field, there is an active discussion on the direction of AI education according to the leaner’s target. Also, various platforms and programs on experience are being distributed. As a prior study, we propose the AI experience educational model. However, there are insufficient steps to evaluate students’ understanding. Therefore, in this paper, we proposed assessment system that can verify the validity of the proposed educational model. The proposal system was designed by constructing an assessment module based on the Item Response Theory for objective student evaluation.